2018
DOI: 10.1177/0022002718789751
|View full text |Cite
|
Sign up to set email alerts
|

A Clash of Norms? How Reciprocity and International Humanitarian Law affect American Opinion on the Treatment of POWs

Abstract: Reciprocity is one of the oldest principles of warfare, but humanitarian norms embedded in international humanitarian law (IHL) prohibit reciprocity over various wartime acts. When it comes to the treatment of prisoners of war (POWs), how do these conflicting norms shape public opinion? One perspective is that citizens who learn about IHL acquire an unconditional aversion to abusing POWs. Alternatively, people may understand IHL as a conditional commitment that instead strengthens their approval for reciprocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
1
9
0
1
Order By: Relevance
“…The experiment indicated that, 4. Bell and Quek 2018;Chaudoin 2014;Chu 2019;Flores-Macías and Kreps 2017;Gelpi, Feaver, and Reifler 2009;Herrmann 2017;Herrmann, Tetlock, and Visser 1999;Johns andDavies 2012, 2014;Kertzer and Brutger 2016;Kertzer et al 2014;Levendusky and Horowitz 2012;McDermott and Hatemi 2017;Milner and Tingley 2016;Prather 2019;Press, Sagan, and Valentino 2013;Stein 2019;Tingley 2017;Tomz 2007;Tomz and Weeks 2013;Trager and Vavreck 2011;Weiss andDafoe 2019. 5.…”
mentioning
confidence: 99%
“…The experiment indicated that, 4. Bell and Quek 2018;Chaudoin 2014;Chu 2019;Flores-Macías and Kreps 2017;Gelpi, Feaver, and Reifler 2009;Herrmann 2017;Herrmann, Tetlock, and Visser 1999;Johns andDavies 2012, 2014;Kertzer and Brutger 2016;Kertzer et al 2014;Levendusky and Horowitz 2012;McDermott and Hatemi 2017;Milner and Tingley 2016;Prather 2019;Press, Sagan, and Valentino 2013;Stein 2019;Tingley 2017;Tomz 2007;Tomz and Weeks 2013;Trager and Vavreck 2011;Weiss andDafoe 2019. 5.…”
mentioning
confidence: 99%
“…Concerns about fairness are usually seen as having evolutionary origins: people must be able to detect and punish cheaters if they want to enjoy the spoils from cooperation and guard themselves against exploitation (Haidt 2012), and fairness concerns typically begin to appear in children around the age of five (Fehr, Bernhard, and Rockenbach 2008). Political scientists have thus linked fairness concerns to a range of phenomena in international politics, including crisis bargaining (Gottfried and Trager 2016), post-war peace negotiations (Albin and Druckman 2012), diplomacy (Kertzer and Rathbun 2015), international humanitarian law (Chu 2019), international cooperation (Efrat and Newman 2016), and foreign direct investment (Chilton, Milner, and Tingley 2020).…”
Section: What's Fair In Foreign Policy?mentioning
confidence: 99%
“…36 Some studies find a 'reciprocity effect': support for torture is more likely when the target's country also uses torture, and less likely when the target's country treats prisoners 2.4 Theory humanely. 37 Information that torture occurs at the hands of one's own government increases support for torture by other nations 38 and leads people to describe torture as more morally justified. 39 The moral reinforcement of torture depending on who perpetrates it has been found both among American and British nationals.…”
Section: Contextual Factorsmentioning
confidence: 99%